Formation of Professional Competence of the Future Teachers of Physical Culture in the Context of Preparation for Professional Self-Improvement - Shapovalova, Iryna (Pedagogical Discourse, 2014)
The article reflects the views of the scientists on the problem of formation of professional competence of the future teachers of physical training and self-development of the student in the learning process, the essence of the concept of «professional competence» is defined, the features of the process of preparation of the future teachers of physical culture to professional self-development throughout life. Scientific approaches to self-development, self-education of the personality of a student in the learning process and self-realization during their future career have been characterized. The article defines the process of professional training of teachers of physical education, in which the significant role belongs to the formation of professional competence, as the main factor in professional growth and successful professional pedagogical activity, conscious willingness to continuous creative, personal and professional self-improvement. Psychological and pedagogical conditions of efficiency of preparation of the future teachers of physical training to the professional activity have been defined; the necessity of usage of competence-based approach to professional training of the future teachers of physical culture, suggesting formedness of a graduate professional competencies, as a set of general knowledge and skills, universal readiness to solve social and professional problems, have been emphasized.